Coastal Environments - Zhang, Yuanzhi; San Liang, X. (IntechOpen, 2021)
In recent years, coastal environments have drawn an increasing awareness globally, regionally, or locally as in many coastal regions, the rapid industrial, urban, and agricultural development has caused dramatic land use and land cover (LULC) changes and various water pollution events in coastal environments. These environmental consequences of human activities exacerbate the effects of regional and global climate change on the hydrological cycle between the land and ocean, and these effects are frequently hazardous or destructive to coastal regions around the world. Remote sensing and geographic information systems (GIS) technologies are thoroughly adopted and applied to monitor the dynamic change of coastal environments, such as coastal LULC, water quality, and marine ecosystem.